2018
DOI: 10.1136/gutjnl-2017-315655
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal ultrasound in inflammatory bowel disease: an underused resource with potential paradigm-changing application

Abstract: Evolution of treatment targets in IBD has increased the need for objective monitoring of disease activity to guide therapeutic strategy. Although mucosal healing is the current target of therapy in IBD, endoscopy is invasive, expensive and unappealing to patients. GI ultrasound (GIUS) represents a non-invasive modality to assess disease activity in IBD. It is accurate, cost-effective and reproducible. GIUS can be performed at the point of care without specific patient preparation so as to facilitate clinical d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
159
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 138 publications
(170 citation statements)
references
References 121 publications
2
159
0
1
Order By: Relevance
“…Therefore, expertise is necessary for the assessment of intestinal lesions to overcome these obstacles . Although recently the International Bowel Ultrasound Group has proposed an internationally recognized education for learning intestinal US, such programs have not yet been widely available . We found that the time to scan the intestine was significantly shortened by using RVS in subjects without apparent intestinal diseases.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Therefore, expertise is necessary for the assessment of intestinal lesions to overcome these obstacles . Although recently the International Bowel Ultrasound Group has proposed an internationally recognized education for learning intestinal US, such programs have not yet been widely available . We found that the time to scan the intestine was significantly shortened by using RVS in subjects without apparent intestinal diseases.…”
Section: Discussionmentioning
confidence: 85%
“…US is a noninvasive, radiation‐free, and inexpensive modality compared with CT, MRI, and endoscopy . Intestinal US has been reported useful for diagnosing of IBD and assessment of IBD disease activity . A recent meta‐analysis showed that US has a high diagnostic accuracy for detecting CD .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We read with great interest a recent review by Bryant et al 1 presenting a pragmatic guide of GI ultrasound (GIUS) in IBD clinical practice. We agree with the authors that the uptake of GIUS outside Europe has been slow and GIUS is underused in many countries.…”
mentioning
confidence: 99%
“…First, gastroenterologist-performed ultrasound and point-of-care ultrasound should be encouraged, as has been successfully implemented in other chronic diseases. GIUS performed by gastroenterologist compared with radiologist could potentially provide more relevant information for management decision 1. Second, there is a need to establish standardised educational training pathways of GIUS.…”
mentioning
confidence: 99%